Development of magneto-nanosensors by using neem leaves extract for biomedical applications / Nurul Izza Taib ... [et al.] - Taib, Nurul Izza; Abdul Latif, Famiza; Mohamed, Zakiah; Zambri, Nur Diyana Syazwani (2020)
An economic, safe and eco-friendly co-precipitation method for the synthesis of iron oxide nanoparticles (Fe3O4-NPs) was performed using non-toxic neem leaves extract as a reducing and stabilizing agent. The successful synthesis was confirmed by infrared spectra analysis with strong peak observed between 400–600 cm−1 that corresponds to magnetite nanoparticles characteristics. X-Ray Diffraction (XRD) analysis showed that the nanoparticles are high purity with crystalline cubic structure phase in nature. Transmission Electron Microscopy (TEM) image displayed the synthesized Fe3O4-NPs were mostly spherical and oval shape with diameter was in the range from 9-14 nm which agrees with calculated Scherrer equation with average diameter of around 11 nm. The hysteresis loops of the nanoparticles were measured using Vibrating Sample Magnetometer (VSM) and the results showed a superparamagnetic behavior at room temperature, suggesting the potential applications for magnetic targeting drug delivery system.